Advances in multidisciplinary therapy for meningiomas - Brastianos, Priscilla K.; Galanis, Evanthia; Butowski, Nicholas; Chan, Jason W.; Dunn, Ian F.; Goldbrunner, Roland; Herold-Mende, Christel; Ippen, Franziska M.; Mawrin, Christian; McDermott, Michael W.; Sloan, Andrew; Snyder, James; et al. (Neuro-Oncology, 2019)
Surgery has long been established as the first-line treatment for the majority of symptomatic and enlarging meningiomas, and evidence for its success is derived from retrospective case series. Despite surgical resection, a subset of meningiomas display aggressive behavior with early recurrences that are difficult to treat. The decision to radically resect meningiomas and involved structures is balanced against the risk for neurological injury in patients. Radiation therapy has largely been used as a complementary and safe therapeutic strategy in meningiomas with evidence primarily stemming from retrospective, single-institution reports. Two of the first cooperative group studies (RTOG 0539 and EORTC 22042) evaluating the outcomes of adjuvant radiation therapy in higher-risk meningiomas have shown promising preliminary results. Historically, systemic therapy has resulted in disappointing results in meningiomas. However, several clinical trials are under way evaluating the efficacy of chemotherapies, such as trabectedin, and novel molecular agents targeting Smoothened, AKT1, and focal adhesion kinase in patients with recurrent meningiomas.